Shale reservoir characterization and implications for the exploration and development of the upper Permian Wujiaping Formation, Longmen–Wushankan area, eastern Sichuan Basin - Tang, Wen; Tuo, Cong; Ma, Shaoguang; Yao, Yongjun; Liu, Dongxi; Yang, Xinrui; Yang, Licheng; Li, Hu (Frontiers in Earth Science, 2024)
Recent exploration efforts have revealed significant industrial gas flow from the Wujiaping Formation marine shale in the Longmen–Wushankan area of the eastern Sichuan Basin, underscoring its considerable exploration potential. In this study, the reservoir characteristics and exploration potential of the Wujiaping Formation shale gas in this area are further evaluated. On the basis of well rock electrical properties, experimental analyses, and depositional and structural patterns in the eastern region, we characterize the reservoir properties and identify the primary factors controlling shale gas accumulation. The results indicate that the Wujiaping shale is characterized by a high organic matter content, favorable pore types, high porosity, and a high content of brittle minerals, which are conducive to subsequent development and fracturing. A positive correlation is observed between the total organic carbon (TOC) content, porosity, brittle mineral content, and shale gas content. The TOC content is strongly correlated with the gas content (the correlation coefficient is 0.75). The high shale gas yield of the Wujiaping Formation is attributed to a combination of favorable sedimentary environments, pore conditions, roof and floor conditions, and fracturing capabilities. However, compared with the Longmaxi Formation in the Sichuan Basin, the Wujiaping Formation shale is characterized by a lower porosity, thinner shale, and deeper burial, posing challenges for exploration and development. In this study, criteria for evaluating Wujiaping Formation shale gas are established, and four favorable exploration areas are identified. Overall, the Permian Wujiaping Formation marine shale in the Longmen–Wushankan area holds promising exploration and development potential. Further exploration and an enhanced understanding of this formation will provide valuable guidance for future marine shale gas exploration and development in this area.